Cellulose Conversion to 5 Hydroxymethyl Furfural (5-HMF) Using Al-Incorporated SBA-15 as Highly Efficient Catalyst. (7th August 2019) - Pham, Son Tung; Nguyen, Manh B.; Le, Giang H.; Pham, Trang T. T.; Quan, Trang T. T.; Nguyen, Trinh Duy; Son, Thanh Le; Vu, Tuan Anh
Abstract : Al-incorporated SBA-15 samples (xAl/SBA-15) were successfully prepared by " atomic implantation " method. The samples were characterized by X-ray diffraction spectroscopy (XRD), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), N2 adsorption-desorption isotherms (BET), and temperature-programmed desorption (NH3 -TPD). In this catalyst, metal oxide species were highly dispersed on the SBA-15 surface and existed as isolated atoms. It was shown that the Al incorporation lead to the formation of medium and strong acid sites. The catalytic activity and selectivity were tested in a mild hydrothermal process for degradation of cotton cellulose to 5-hydroxymethyl furfural (5-HMF). A cellulose conversion of 68.5% and 5-HMF selectivity of 62.1% after 2 h of reaction at 170°C were achieved. The very high 5-HMF yield (42.57%) obtained in this paper is much higher than that was reported in the literature.